Prophylactic mastectomy for the prevention of breast cancer: Review of the literature - Alaofi, Rawan K.; Nassif, Mohammed O.; Al-Hajeili, Marwan R. (Avicenna Journal of Medicine, 2018)
The high incidence and recurrence rate of breast cancer has influenced multiple strategies such as early detection with imaging, chemoprevention and surgical interventions that serve as preventive measures for women at high risk. Prophylactic mastectomy is one of the growing strategies of breast cancer risk reduction that is of a special importance for breast cancer gene mutation carriers. Women with personal history of cancerous breast lesions may consider ipsilateral or contralateral mastectomy as well. Existing data showed that mastectomy effectively reduces breast cancer risk. However, careful risk estimation is necessary to wisely select individuals who will benefit from preventing breast cancer.
Keywords: BRCA; breast neoplasms; ductal carcinoma in situ; prophylactic mastectomy; risk reduction